2006
DOI: 10.1051/kmae:2006023
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Survival and Growth in Juvenile Astacus Leptodactylus (Esch.) and Pacifastacus Leniusculus (Dana) Under Controlled Conditions

Abstract: The aim of this study was to compare survival and growth of juvenile narrow-clawed crayfish (Astacus leptodactylus) and signal crayfish (Pacifastacus leniusculus) fed only with experimental pellets (45% of proteins, 6% of fat, 20% crude fibre) under controlled conditions. The animals were reared in 12 (50 l) circular plastic tanks, the narrow-clawed crayfish set-ups being designated A1 and A2, the signal crayfish set-ups P1 and P2. The initial stocking densities for each species were 600 (A1, P1) and 1,200 (A2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
31
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 10 publications
(13 reference statements)
8
31
0
Order By: Relevance
“…4 for P. leniusculus). Ulikowski et al (2006) reported similar observations with older individuals of both species after 6 months of rearing. Therefore, Ulikowski et al (2006) concluded that the growth rate of A. leptodactylus under optimal conditions is comparable to that of P. leniusculus.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…4 for P. leniusculus). Ulikowski et al (2006) reported similar observations with older individuals of both species after 6 months of rearing. Therefore, Ulikowski et al (2006) concluded that the growth rate of A. leptodactylus under optimal conditions is comparable to that of P. leniusculus.…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, it can be concluded that the juveniles of both species have similar growth rates. Ulikowski et al (2006) also found a similar growth rate in P. leniusculus and A. leptodactylus during the first 3 months after hatchings. The SGR was 1.3 (initial density: 600 stage 2 m -2 ) and 1.4 (initial density: 1,200 stage 2 m -2 ) for A. leptodactylus and 1.7 for P. leniusculus (at both densities).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our results from brackish water corroborate this statement. The survival of juveniles may be affected by the insufficient number of shelters (Figler et al 1999), higher molting frequency (Barki et al 1997) and high density promoting cannibalism (Ulikowski et al 2006). Young crayfish are very sensitive organisms (Świerczyński 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, several trials have shown that the supply of dry diets as the sole food from the onset of exogenous feeding yields poor survival or growth rates (e.g. Ackefors et al, 1989;Taugbøl and Skurdal, 1992;Celada et al, 1993;Ulikowski et al, 2006;Sáez-Royuela et al, 2007). Recently, acceptable survival and growth rates were recorded by means of the additional supply of live Artemia nauplii to a commercial dry diet for salmonids (Sáez-Royuela et al, 2007;González et al, 2008), thus allowing for the first time reliable possibilities of intensification.…”
Section: Introductionmentioning
confidence: 99%